Linguistics Realization Analysis on Slang Word; Social Media Whatsapp - ELFRIDA BR SILALAHI; Nela Silalahi (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
Nowadays supporting in communication ways in easier by Electronics many applications using to communication as Facebook, WhatsApp, Instagram, Line and others. The development of era has been influence in communication and interaction way. Many of slang word used in communication in verbal, orally or written. Slang is one of effect of social life in language it is part of language variety which are informal which used to communication as members in social community. With slang people used, is one indicating people are modern and impressive. Objectives of this Research is gives points about Sociolinguistics Slang Word; using on Social Media especially in WhatApp Application. From these article wish we found what kinds of Slang word used on WhatsApp Media. Method used in this research is qualitative method to analyze data. Data obtained came from WhatsApp Application that used teenagers in Author WhatsApp Group. For collecting the data, Author used the method of observation. Author found some slang words that using teenagers in popular slang as : “Jelly” meaning Jealous, “Swag” means Cool, “Y” means why, “Zzz” Means Sleeping, “Imo” means In my opinion and others.